Electronic absorption study on hydration, solvation behavior for some keto and thioketo pyrimidine derivatives - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In this study, the hydration and solvation properties of recently synthesized 5-benzoyl-1-(methylphenylmethyleneamino)-4-phenyl-1H-pyrimidine-2-one, (I) and 5-benzoyl-1-(methylphenylmethyleneamino)-4-phenyl-1H-pyrimidine-2-thione, (II), were studied with respect to pH and time by using UV-vis spectroscopy method in aqueous (95.0% v/v water) and methanol (95.0% v/v methanol) media. The roles of the keto oxygen of I and the thioketo sulfur of II on the hydration and solvation behavior were discussed. The experiments were performed at 25 degrees C and at pH values between 1.0 and 13.0. Compound I was found to undergo hydration best in strongly acidic solutions. However, compound II was found to undergo solvation best in basic solutions. The preferred hydration and solvation mechanisms were discussed based on UV-vis data and the related mechanisms undergoing in strongly acidic and basic regions were proposed for the each compound. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hydration; Pyrimidines; Semicarbazone; Thiosemicarbazone; UV-vis spectroscopy; ACID-BASE EQUILIBRIA; REFERENCE VALUE STANDARDS; DISSOCIATION-CONSTANTS; OXALYL COMPOUNDS; PH MEASUREMENTS; METHANOL-WATER; COMPLEXES; CARBONYL; HYDROGEN; THIOSEMICARBAZONES